2001
DOI: 10.1097/00000658-200105000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Laparoscopic Cholecystectomy: Patient Outcomes After Implementation of a Clinical Pathway

Abstract: ObjectiveTo determine the success of a clinical pathway for outpatient laparoscopic cholecystectomy (LC) in an academic health center, and to assess the impact of pathway implementation on same-day discharge rates, safety, patient satisfaction, and resource utilization. Summary Background DataLaparoscopic cholecystectomy is reported to be safe for patients and acceptable as an outpatient procedure. Whether this experience can be translated to an academic health center or larger hospital is uncertain. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 24 publications
10
89
0
12
Order By: Relevance
“…Most studies are focusing on one single operation and on length of hospital stay [6][7][8][9][10][11][12][13][14][15] ( Table 4). Costs were only analyzed with the help of general model calculations and resource utilization was not analyzed in detail [22][23][24]. All these studies found a reduction of hospital stay ranging between 14% and 46% as well as cost savings up to 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are focusing on one single operation and on length of hospital stay [6][7][8][9][10][11][12][13][14][15] ( Table 4). Costs were only analyzed with the help of general model calculations and resource utilization was not analyzed in detail [22][23][24]. All these studies found a reduction of hospital stay ranging between 14% and 46% as well as cost savings up to 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy decreases postoperative pain, decreases the need for postoperative analgesia, shortens the hospital stay from 1 week to less than 24 hours, and returns the patient to full activity within 1 week compared with 1 month after open cholecystectomy [11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…3 Now, out-patient LC is increasing in the United States due to expensive admission costs. 6,8 However, some studies showed difficulty of LC on initial admission in patients with complicated gallstone diseases due to their severity of the disease. 4 Some institutions demonstrated that only 40% of patients with AC underwent cholecystectomy on initial admission, 9,10 despite the advantages of early cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Since laparoscopic procedure for cholecystectomy has been introduced, it has become the treatment of choice for symptomatic gallbladder stone. 6 The positive effects of implementing critical pathways has been assessed in laparoscopic cholecystectomy (LC) for chronic cholecystitis (CC). 5 However, only a few studies are present on the usefulness on critical pathway in acute cholecystitis (AC) are present, 4 because implementation of CP to AC is regarded as difficult due to wide variation of clinical manifestation.…”
Section: Introductionmentioning
confidence: 99%